2021
DOI: 10.3390/s21144903
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Archive Box for Museum Artifact Monitoring Using Battery-Less Temperature and Humidity Sensing

Abstract: For the first time, this paper reports a smart museum archive box that features a fully integrated wireless powered temperature and humidity sensor. The smart archive box has been specifically developed for microclimate environmental monitoring of stored museum artifacts in cultural heritage applications. The developed sensor does not require a battery and is wirelessly powered using Near Field Communications (NFC). The proposed solution enables a convenient means for wireless sensing with the operator by simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In the presented design, both voltage and frequency scaling (VFS) techniques were used to minimize the DC power consumption of the developed sensor with the aim to maximize the wireless communication range. To achieve sub-mW DC power consumption, the NFC-enabled humidity sensor was designed with optimal settings: MCU peripheral clock ( f CLK ) = 0.524 MHz; I2C core input clock ( f I2C_IN ) = 1.028 MHz; MCU core voltage ( V CORE ) = 1.2 V; supply voltage ( V DD ) of 2.1 V. As a result, the NFC-enabled humidity sensor required a peak DC power of just 900 µW, which is one of the lowest reported in the literature [ 59 ]. A Samsung Galaxy S21 smartphone was used to measure the wireless communication range, achieving a maximum of 4.5 cm in free-space.…”
Section: Resultsmentioning
confidence: 99%
“…In the presented design, both voltage and frequency scaling (VFS) techniques were used to minimize the DC power consumption of the developed sensor with the aim to maximize the wireless communication range. To achieve sub-mW DC power consumption, the NFC-enabled humidity sensor was designed with optimal settings: MCU peripheral clock ( f CLK ) = 0.524 MHz; I2C core input clock ( f I2C_IN ) = 1.028 MHz; MCU core voltage ( V CORE ) = 1.2 V; supply voltage ( V DD ) of 2.1 V. As a result, the NFC-enabled humidity sensor required a peak DC power of just 900 µW, which is one of the lowest reported in the literature [ 59 ]. A Samsung Galaxy S21 smartphone was used to measure the wireless communication range, achieving a maximum of 4.5 cm in free-space.…”
Section: Resultsmentioning
confidence: 99%
“…The paper by Gawade et al [24] reports on a smart museum archive box that features a fully integrated, wireless powered temperature and humidity sensor. The smart archive box has been specifically developed for microclimate environmental monitoring of stored museum artifacts in cultural heritage applications.…”
Section: Sensor Network and Smart/intelligent Sensorsmentioning
confidence: 99%
“…From the application perspective, amongst the popular wireless communication platforms such as NarrowBand IoT (NB-IoT), SigFox (a French global network provider), Long-Range Wide Area Network (LoRaWAN), Bluetooth Low Energy (BLE), and Near Field Communication (NFC), the NFC technology offers a unique benefit of a very low power requirement [33] while transmitting data. Recent studies have reported that typically, 900 μW of power is consumed by NFC-based sensor interfaces while offering a communication range up to 4.5 cm [34], [35], [36], [37]. The communication range of the NFC platform largely depends on the several parameters, such as reader type, NFC antenna size, coupling between NFC reader and tag, RFID air interface, and power consumption of the front-end electronics.…”
Section: Introductionmentioning
confidence: 99%
“…The communication range of the NFC platform largely depends on the several parameters, such as reader type, NFC antenna size, coupling between NFC reader and tag, RFID air interface, and power consumption of the front-end electronics. With NFC type 5 enabled smartphone as a reader, a maximum communication range of 7 cm could be achieved, which increases to 1 m when a 13.56 MHz reader (ISO/IEC 15693) is employed [34], [38]. Nowadays, the inclusion of the NFC technology in smartphones enables on-call data acquisition through reader/smartphones, which substantially reduces the installation cost of the NFC sensors [34], [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation